Effects of Eco-Tourism on Local Community in District Chitral Lower of Pakistan (Journal of Asian Development Studies, 2024)
Ecotourism plays an important role in the development of rural areas. It generates rural employment and improves the socioeconomic condition of the local community. This study was initiated to assess the effects of eco-tourism on the local community in Chitral Lower district, Pakistan, and to identify various effects and problems for the promotion of eco-tourism in the study area. A total of 230 sample respondents from three villages were randomly selected. Data were collected with the help of questionnaires, random surveys, and interviews with key informants and observations. Through descriptive statistics and binary logistic regression, data were analyzed. From the coefficients of the logistic regression model, only fourindependent variables, namely income, education, lodging facility, and tour guide facility, had a statistically significant relationship with ecotourism. Having a high level of education gives community members a variety of opportunities to engage in high-value and high-paying ecotourism activities to increase their income level. Having proper lodging and tour guide facilities increases the engagement of tourists and visitors. Therefore, the findings clearly indicate that more education, income opportunities, lodging facilities, and availability of tour guides facilities will help increase eco-tourism in the area. This study recommends that to govern and manage the eco-tourism areas, in order to reach their full potential and provide long-term benefits to the local community, the government should explore the potential ecotourism benefits and create appropriate policies to furnish the ecotourism while security provisions to the community also help in the ecotourism improvement